SISTEM PELAYANAN KESEHATAN PUSKESMAS AKELAMO DI KECAMATAN SAHU TIMUR KABUPATEN HALMAHERA BARAT - Abram, Orpa Ovelia; Posumah, Johnny Hanny; Palar, Novie (Sam Ratulangi University, 2017)
Abstract :Health care system is a very important in dunya health through this system in expecting health qualityespecially in Indonesia through this system health development goals can be achieved by effective and fixedtarget. Succse health care system depends on the various components that enter in health services Includingnurses, doctors, or other supportive health teams. Satisfy people's expectations and needs. One effort that isdone is to provide facilities, health services in the intention of course is a fast service, precise, cheap andfriendly. The purpose of this study is to provide input for puskesmas akelamo benefit of this research is toprovide input for puskesmas or stakeholder in sub-district east of west halmahera regency. The method usedis qualitative method with the type of descriptive approach and the location of research in the sub-district ofeastern district of west halmahera data collection is done is the observation and in-depth interviews ofinformants.Based on the results of the study there are several serious factors to be improved in which facilitiesand infrastructure facilities are inadequate drugs limited and lack of cooperation across sector programsless attention from the government, so that the impact becomes a barrier in service to the community.Keywords: health service system of puskesmas